(untitled) (Journal of Applied and Natural Science, 2018)
Biological communities reflect overall ecological integrity (i.e. chemical, physical and biological integrity). Since the diatom species exhibit variation in tolerances to physical and chemical change in water, they are excellent indicators changes in their environment. Based on the dominant categories for each characteristic, the ecological state of the stream can be determined. This study evaluates the ecological state of the streams in Doon Valley. The diatom samples collected at regular monthly intervals from the twelve streams located in the eastern and western Doon were treated with acid-peroxide and mounted in Naphrax for species count at x1500. About 250-300 valves of diatom species were counted and Van Dam ecologic values were computed by OMNIDIA ver. 5.3. pH was alkaliphilous (4), salinity - fresh brackish (2) and oxygenation - continuously high (1) for most of the streams. Saprobity and trophic status was largely ?-mesosaprobous (2) and eutraphentic (5), respectively. The Leclercq index also shows non-existent (<10%) to low (10-20%) organic pollution, degradation (IDSE=3.5-3.0) and moderate anthropogenic eutrophication (20.1-45%) in most of the streams attributed to urbanization stress (62 MLD sewage). The water quality based on indices; IBD (Indice biologique diatomèes), IPS (Indice de polluo-sensibilite) and TDI (Trophic Diatom Index) showed the moderate water quality in the streams of the Valley. Like EU Water Framework Directive 2000/60/EC (WFD) India should also have the objective to ensure ecosystem integrity through bio-assessment and not just mere pollution control.